PLS path modeling: A software review - Dirk Temme; Henning Kreis; Lutz Hildebrandt (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
After years of stagnancy, PLS path modeling has recently attracted renewed interest from applied researchers in marketing. At the same time, the availability of software alternatives to Lohmöller's LVPLS package has considerably increased (PLS-Graph, PLS-GUI, SPAD-PLS, SmartPLS). To help the user to make an informed decision, the existing programs are reviewed; their strengths and weaknesses are identified. Furthermore, analyzing simulated data reveals that the signs of weights/factor loadings and path coefficients can vary considerably across the different programs. Thus, applied researchers should treat the interpretation of their results with caution. Compared to programs for analysis of covariance structure models (LISREL approach), PLS path modeling software is on equal footing regarding ease of use, but clearly lags behind in terms of methodological capabilities.
Keywords: C31; C87; M31; 330; PLS path modeling; Marketing; Formative indicators; Reflective indicators